The Impact of Consumption and Tax Revenue on Gross Domestic Investment in Vietnam - Khang, Nguyen The (Journal of Posthumanism, 2025)
This study examines the impact of consumption and tax revenue on domestic investment in Vietnam from 2000 to 2024 by employing a vector error correction model (VECM) to investigate both short- and long-run dynamics. These findings indicate that tax revenue positively influences investment in the long run, implying that an efficient tax system can facilitate capital accumulation and drive economic growth. Conversely, household consumption exerts a significant negative effect on investment, likely due to the crowding-out effect, in which excessive consumption constrains the capital available for productive investment. Furthermore, government expenditure positively contributes to investment, underscoring the crucial role of public spending in fostering private-sector development. However, the study finds no significant short-term effects of tax revenue, household consumption, or public expenditure on investment, suggesting that fiscal policies primarily shape investment trends in the long term. This study fills a critical gap in Vietnamese economic policy research by simultaneously examining the effects of taxation and consumption on investment. The findings underscore the need for tax policy reforms that incentivize investment, prudent public spending management, and regulatory measures to control excessive household consumption and ensure efficient capital allocation. In addition, maintaining macroeconomic stability and enhancing fiscal-monetary policy coordination are essential for improving investment efficiency. These findings offer policymakers practical insights into fostering long-term economic growth.